Taming a sea-horse - Parker, Robert B. (Dell Publishing, 1986)
Spenser's interest in teenage prostitute April Kyle leads him to Robert Rambeaux, ersatz Juilliard student and April's pimp, and to Ginger Bucky, another of Rambeaux's hookers, who suddenly turns up dead
Keywords: Adult Mystery